2020
DOI: 10.2196/15777
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Self-Monitoring by Young Adolescents and Parents to Assess and Improve Family Functioning: Qualitative Feasibility Study

Abstract: Background The natural integration of mobile phones into the daily routines of families provides novel opportunities to study and support family functioning and the quality of interactions between family members in real time. Objective This study aimed to examine user experiences of feasibility, acceptability, and reactivity (ie, changes in awareness and behaviors) of using a smartphone app for self-monitoring of family functioning with 36 participants … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…This study identified that adolescents who received low levels of support from their parents spent longer time on their smartphone. This is consistent with another research finding that adolescents with more parental support have lower smartphone screen time ( 25 , 47 , 48 ). When adolescents recognise support from their parents, they experience a high level of psychological well-being with improved self-control, ultimately decreasing risks of problematic smartphone use ( 19 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study identified that adolescents who received low levels of support from their parents spent longer time on their smartphone. This is consistent with another research finding that adolescents with more parental support have lower smartphone screen time ( 25 , 47 , 48 ). When adolescents recognise support from their parents, they experience a high level of psychological well-being with improved self-control, ultimately decreasing risks of problematic smartphone use ( 19 ).…”
Section: Discussionsupporting
confidence: 92%
“…When adolescents recognise support from their parents, they experience a high level of psychological well-being with improved self-control, ultimately decreasing risks of problematic smartphone use ( 19 ). When parents deliver a clear message to ban excessive use of smartphones at home, applying needed rules, the smartphone screen time of adolescents tends to decrease ( 48 ). All this implies that the parental support has direct and indirect effects on the smartphone behaviour of the children.…”
Section: Discussionmentioning
confidence: 99%
“…By the way, a report on the relationship between children and mobile phone, pointed out that over 80% of the participants reported an increased awareness of their relationship dynamics with their child/parent, their own behaviour, or their communication styles after the survey. [ 25 ] In our questionnaire, 19% of responders use MD for school research and 8% for parents’ communications. As for the others, 24% use MD to communicate with friends, 23% to join social network, and 8% to play video games.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, EMA may help families to reflect on their own daily routines [16]. After 2 weeks of self-monitoring 80% of the participants reported increased awareness of their relationship, behaviors, and communication styles [22]. One child, in this study, realized he was not doing sufficient chores, and started to help unloading the dishwasher.…”
Section: Ema In Practicementioning
confidence: 82%
“…To address this, sampling schemes can be tailored to the daily routines of individual families, participants can indicate themselves when interactions have taken place (i.e., event-based sampling), and technological solutions [e.g., Bluetooth proximity triggered sampling) are under development. Moreover, EMA can be applied to assess momentary interaction quality as well as concrete parenting behaviors [22], but there is lack of research on the quality of these EMA-instruments. To understand parenting within the broader families system, ideally, caregivers and adolescents report on the same interactions and events [51].…”
Section: Challenges Aheadmentioning
confidence: 99%